2009
DOI: 10.1007/s12230-009-9078-y
|View full text |Cite
|
Sign up to set email alerts
|

A Patchwork of Streptomyces Species Isolated from Potato Common Scab Lesions in North America

Abstract: To determine distribution and prevalence of Streptomyces species associated with common scab in North America, more than 1,400 isolates were made from scabby potato tubers. Samples were obtained from locations across the continent, and from multiple sites in close geographic proximity. Most potentially pathogenic isolates belonged to four species previously associated with common scab, S. scabies, S. europaeiscabiei, S. stelliscabiei, and S. sp. IdahoX. Additionally, small numbers of potentially pathogenic iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 44 publications
5
98
1
2
Order By: Relevance
“…Most studies base pathogenicity determination of isolates on the presence of txtAB and only conduct pathogenicity pot trials tests on selected isolates (Wanner 2009;Leiminger et al 2012;Dees et al 2013), although Park et al (2003) reported two potato scab-causing isolates from Korea that did not produce thaxtomin. Leiminger et al (2012) and Wanner (2009) also isolated pathogenic but txtAB-negative S. acidiscabies, S. stelliscabiei and S. bottropensis from Germany and North America respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies base pathogenicity determination of isolates on the presence of txtAB and only conduct pathogenicity pot trials tests on selected isolates (Wanner 2009;Leiminger et al 2012;Dees et al 2013), although Park et al (2003) reported two potato scab-causing isolates from Korea that did not produce thaxtomin. Leiminger et al (2012) and Wanner (2009) also isolated pathogenic but txtAB-negative S. acidiscabies, S. stelliscabiei and S. bottropensis from Germany and North America respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between the Streptomyces species, environment and host are complex and result in unpredictable disease incidences, severity and symptomatology between regions and years, making this disease difficult to understand (Wanner 2009). Common scab is not caused by a single species, but rather a species complex within the Streptomyces genus (Loria et al 1997;Wanner 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations